2019
DOI: 10.1039/c8sm01502c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction processes among self-propelled particles

Abstract: We study a system of self-propelled disks that perform run-and-tumble motion, where particles can adopt more than one internal state. One of those internal states can be transmitted to another particle if the particle carrying this state maintains physical contact with another particle for a finite period of time. We refer to this process as a reaction process and to the different internal states as particle species making an analogy to chemical reactions. The studied system may fall into an absorbing phase, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…We show that different collective states characterized by different time-dependent, self-organized spatial structures result in dramatically different contagion dynamics, both in terms of the overall magnitude of the outbreaks and of the detailed spatial characteristics of the spreading process. Our results also confirm that the importance of the contagion time-scale in agent-based contagion process, as discussed [13], in a more general and complex setting.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We show that different collective states characterized by different time-dependent, self-organized spatial structures result in dramatically different contagion dynamics, both in terms of the overall magnitude of the outbreaks and of the detailed spatial characteristics of the spreading process. Our results also confirm that the importance of the contagion time-scale in agent-based contagion process, as discussed [13], in a more general and complex setting.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, core parameters of a SIR-contagion process: contact rate and contact duration are in fact emergent properties of the self-organized, spatial dynamics. This has been investigated for example in gas-like systems of self-propelled agents [12,13,14], where among other it was shown that contact rate and contact duration may be affected in different ways by the speed of individual agents, leading to nontrivial dependence of the contagion dynamics on this single movement parameter [13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, if the WCA potential does not drastically change the speed v 0 , we approximately obtain that �|� v ij rel | 2 � ≈ 2v 2 0 since �v 2 i � ≈ v 2 0 . By considering the total area swept for N particles in a time interval τ c as A sw = N(2R + πR 2 ) , we define the maximum contagion probability p c = A sw /A = 1 , and using the relation = √ 2v 0 τ c , we recover the analytical expression of the contagion rate given in (2).…”
Section: Microscopic Contagion Ratementioning
confidence: 99%
“…Nevertheless, a more realistic model must consider the mobility of infectious particles and particle density within its environment. In this direction, self-propelled particles 2 , 3 , the random motion of non-interacting particles 4 , 5 , cellular automaton 6 , 7 , dynamical density functional theory approach 8 , and reaction–diffusion models 9 , 10 have been proposed to introduce the spatial motion of infectious particles. As a matter of universality, active matter models are intuitive and are extensively used to describe a wide range of biological processes ranging from bacteria motion to animal movement 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation